Comparative study between operating and non-operating management in patient with mid shaft clavicle Fractures - Ratish Singh,; Amit Ranjan Mishra,; Chandra Mani Khatri,; Deb Narayan Sah,; Sandeep Sharma, (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Clavicle is one of the common fractures around 4% of total fracture encountered. Road traffic accident as well as fall injury and sports activities result to clavicle fracture. The trauma resulting to clavicle fracture mostly occurred at middle shaft of the clavicle. Treatment modalities should be done for clavicle fracture on all factors that include union, complications, costs, cosmetic and functional outcome. Thus, this prospective study was aimed for comparing the bone union duration, functional outcome, patient satisfaction and never the less the complications seen from both mode of treatment of clavicle fracture Material and Methods: Patient with complete displaced mid-shaft clavicle fractures at emergency and orthopedics department of Janaki medical College and Teaching Hospital from February 2021 to November 2022 were selected for this prospective research. After fulfilling the inclusion criteria, the patients were divided into two groups randomly, with 30 cases in each group of operating and non-operating. Results: This study showed operating group has better outcome and less complication compared with non-operating group in aspect of non-union, mal-union and functional issues. Mean fracture union time in follow-up was noticed as 3.21 months and 4.38 months in operative and non-operative group respectively. The mean Constant shoulder score was 91.3 for operating group. The mean DASH score after was 8.9 operating group. The mean constant shoulder score and DASH score were 77.4 and 23.3 in non-operating group. The P-values for DASH and Constant shoulder score were less than 0.001 which is statically significant. There were few complications in operating group like hypertrophic scar, implant failure and infection. There were significant benefits of operating mid-shaft clavicle fracture over non-operating group. Conclusion: Open reduction and internal fixation of mid-shaft clavicle fracture is an effective treatment. This method has a higher satisfaction rate than conservative treatment.